2016
DOI: 10.1128/aac.01151-16
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Interaction Potential of 22 Antituberculosis Drugs on Organic Anion and Cation Transporters of the SLC22A Family

Abstract: b Twenty-two currently marketed antituberculosis drugs were comprehensively evaluated for their inhibitory effect on organic anionic transporter (OAT)-and organic cation transporter (OCT)-mediated uptake using stably transfected HEK293 cells in vitro. We observed moderate to strong inhibitory effects on OAT1-and OAT3-mediated para-aminohippurate (PAH) uptake and OCT1-and OCT2-mediated N-methyl-4-phenylpylidinium acetate (MPP ؉ ) uptake. Ciprofloxacin, linezolid, para-aminosalicylic acid (PAS), and rifampin wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
(36 reference statements)
2
20
1
Order By: Relevance
“…3), but its estimated DDI index value did not support the existence of a clinical DDI. This is in contrast to the findings described in a recently published study in which we reported a potential DDI between PAS and metformin and in which PAS inhibited metformin uptake via OCT1 and OCT2 in vitro (29). In this study, verapamil, cimetidine, and quinidine strongly inhibited PAS uptake via OCT1 and OCT2, and the DDI index values were much higher than the cutoff values (Table 2), indicating possible clinical DDIs.…”
Section: Figcontrasting
confidence: 56%
See 2 more Smart Citations
“…3), but its estimated DDI index value did not support the existence of a clinical DDI. This is in contrast to the findings described in a recently published study in which we reported a potential DDI between PAS and metformin and in which PAS inhibited metformin uptake via OCT1 and OCT2 in vitro (29). In this study, verapamil, cimetidine, and quinidine strongly inhibited PAS uptake via OCT1 and OCT2, and the DDI index values were much higher than the cutoff values (Table 2), indicating possible clinical DDIs.…”
Section: Figcontrasting
confidence: 56%
“…Human embryonic kidney 293 (HEK) cells were stably transfected according to a previously reported method (34), and we have recently published the findings of a study using such stably transfected cells (29,31,35). In brief, stably transfected HEK-OCT1, HEK-OCT2, HEK-OAT1, HEK-OAT3, HEK-OATP1B1, HEK-OATP2B1, and HEK-OATP1B3 cells were grown in tissue culture flasks in Dulbecco's modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 1% nonessential amino acids, 2 mM L-glutamine, and 100 U/ml penicillin-streptomycin (Invitrogen) at approximately 37°C in an atmosphere supplemented with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the maximum plasma concentration (C max ) and the maximum concentration of unbound drug in plasma (C max,u ) for each drug and the IC 50 values from our in vitro study to predict the possibility of a clinical DDI, according to eq. 2 (Ito et al, 1998;Lau et al, 2007;CDER, 2012;Pan et al, 2013;Chioukh et al, 2014;Parvez et al, 2016):…”
Section: Methodsmentioning
confidence: 99%
“…4A). Previously, we also reported ethambutol inhibitory interactions with SLC transporters and drug-drug interaction potentials in vitro (35). Along with glomerular filtration, tubular secretion is also involved in ethambutol elimination from the kidney, as it has greater secretory clearance (36).…”
Section: Discussionmentioning
confidence: 86%